2003
DOI: 10.5551/jat.10.329
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Dose-Response Study of Rosuvastatin in Japanese Patients With Hypercholesterolemia

Abstract: Rosuvastatin is a novel statin that has been shown to produce large dose-dependent reductions in low-density lipoprotein cholesterol (LDL-C) in Western hypercholesterolemic patients. Rosuvastatin dose response was assessed in a randomized, double-blind phase II trial in which 112 Japanese patients with fasting LDL-C > 160 and < 220 mg/dl and triglycerides < 300 mg/dl received placebo or rosuvastatin 1, 2.5, 5, 10, 20, or 40 mg once daily for 6 weeks. LDL-C change from baseline showed a linear dose response (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 12 publications
5
28
0
5
Order By: Relevance
“…In patients not previously treated with statins, there was a significant 39.9% reduction in LDL-C, which is remarkably similar to the 33 − 56.8% reported in other studies involving mainly Caucasian [14][15][16][17][18] or Japanese 19) patients. This study also shows that most (80.1%) primary and secondary prevention hypercholesterolemic statin-naive patients were able to achieve their therapeutic LDL-C goals with the 10 mg starting dose of rosuvastatin.…”
Section: Discussionsupporting
confidence: 76%
“…In patients not previously treated with statins, there was a significant 39.9% reduction in LDL-C, which is remarkably similar to the 33 − 56.8% reported in other studies involving mainly Caucasian [14][15][16][17][18] or Japanese 19) patients. This study also shows that most (80.1%) primary and secondary prevention hypercholesterolemic statin-naive patients were able to achieve their therapeutic LDL-C goals with the 10 mg starting dose of rosuvastatin.…”
Section: Discussionsupporting
confidence: 76%
“…Reduction in triglycerides and increase in HDL-C were observed at both dose levels, with no dose-response effect being observed. Our results are consistent with previously reported for rosuvastatin treatment (18,19). Treatment with rosuvastatin 40 mg/day produced greater improvement in LDL-C and total cholesterol than rosuvastatin 10 mg/day; however, as expected, both treatments had equal beneficial effects for HDL-C and triglycerides.…”
Section: Discussionsupporting
confidence: 83%
“…11,12) In JUPITER trial (Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin) for men and women with normal LDL-C level (< 130 mg / dL) and elevated high-sensitivity C-reactive protein levels (≥ 0.2 mg / dL), rosuvastatin reduced cardiovascular / cerebrovascular events. 13) However, there are few data on the efficacy and safety of rosuvastatin in Japanese patients, [14][15][16] because the application for approval of the drug was based on overseas data extrapolated to Japanese. A pharmacokinetic study conducted in Japan showed that the blood concentration of the drug in Japanese patients was almost twice that in Caucasians, based on which the initial dose for Japanese patients was set at 2.5 mg / day, half of the dose used in the United States.…”
Section: Methodsmentioning
confidence: 99%